The Role of Medication Observer And Compliance In Medication Of Pulmonary Tuberculosis Patient - Septiyani Putri; La Ode Alifariki; Fitriani Fitriani; Mubarak Mubarak (Jurnal Kesehatan Prima, 2020)
Pulmonary tuberculosis is still a significant health problem in Indonesia; the high rate of pulmonary tuberculosis sufferers causes by the patient's non-compliance factor in taking the drug, allowing resistance and recurrence. Support for the role of medicine intake supervisors has a significant role in increasing compliance with medication for pulmonary tuberculosis patients. The purpose of this research was to determine the relationship between the role of medicine intake supervisors and medication compliance for pulmonary tuberculosis (TB) patients. This research used observational analytic with cross-sectional research design, was conducted in February-March 2019. The sampling method used consisted of 30 respondents using total sampling. WHO analysis used statistical tests with a significant level of α <0.05. The independent variable of this study was the role medicine intake supervisor and the dependent variable was medication compliance for pulmonary tuberculosis patients. Supervisor is that it has a proper role of 26 (86.7%) respondents and those who have fewer roles as many as 4 (13.3) respondents. Respondents who were obedient to taking medicine were 24 (80.0%) respondents, and those who did not obey took medicine as many as 6 (20.0%) respondents. The results of the Fisher Exact statistics show that there is a relationship between the role of medicine intake supervisors (OBSERVER) and medication compliance to patients with pulmonary tuberculosis in p-value = 0.001 (p-value <0.05). This study concludes that the better the role of supervisors taking medication (OBSERVER), the more obedient patients are in taking medication.